Implementasi VPN Menggunakan Metode Point to Point Tunneling Protocol - Andriani, Ria; Sa’di, Ahmad; Putra, Andriyan Dwi (Building of Informatics, Technology and Science (BITS), 2022)
The XYZ office is a government agency covering various fields, ranging from government, economy, development, people's welfare, community life development and public service affairs. However, work activities in agencies were disrupted due to the COVID-19 pandemic which caused the government to impose a Large-Scale Social Restriction (PSBB) policy to suppress the spread of this virus, resulting in agency workers having to work from home. Therefore we need an appropriate means to be able to support these activities. One of them is making a technology design by implementing a VPN on a proxy router with the PPTP (Point to Point Tunnelling Protocol) method so that it can make it easier for employees to communicate without thinking about location. In addition, users can still remotely access the local network even though they are outside the office network. more secure. Based on the results of testing the network security at the XYZ Office before using the VPN Server, it proved that the wiretapping attackers could still obtain data in the form of website login information, proxy logins, or view data contents when exchanging data. Meanwhile, when the user connects to the VPN Server, the eavesdropper cannot see the contents of the data in it, then with the implementation of a VPN with the PPTP method, employees who are working from home can connect and communicate well with each other, with that work and information exchange will become more flexible and faster